Benefits and challenges associated with implementation and ongoing use of automated dispensing cabinet for medicines: A scoping review - Yoo Young Jung; Áine Walsh; Jig Patel; Kit Lai (Exploratory Research in Clinical and Social Pharmacy)
When deciding whether to adopt a digital healthcare technology, there is a need to fully grasp the benefits as well as understand any potential challenges from the outset, to enable appropriate mitigations to be considered as part of implementation plans. Automated dispensing cabinets (ADCs) have been increasingly used in hospitals as a means of streamlining medicines use workflows, facilitating medicine management, saving costs, and improving patient safety. Manufacturers commonly reference the benefits of ADCs but rarely outline the challenges. It is important that senior leaders in healthcare understand both the benefits and challenges of ADCs prior to implementation, to ensure the technology is implemented in areas where the benefits can be most maximally achieved and the challenges mitigated in so far as possible. A scoping review methodology was used to map existing literature focussing on the benefits and challenges of ADC use with medicines. Following a preliminary search to identify key terms, extensive literature searches were conducted in Medline, PubMed, CINAHL, Embase, Global Health, and Web of Science. Among 234 articles identified from the search, 54 articles were included for full data extraction. Extracted information included publication date and origin, study aims & objectives, study setting, medication distribution model, technology infrastructure, overarching category, area of focus, and key findings. The findings were discussed in terms of implications for broad trends and future research directions. Although results indicate that there is an abundance of published literature on benefits and challenges associated with ADC use with medicines, there are only a handful of UK studies. Differences in settings, distribution models, workflows and technology infrastructure limit the overall ability to generalise findings. Further UK-based studies carried out in different settings with varying levels of technological infrastructure is imperative to not only track the impact of ADCs but also to inform practice to ensure the continued delivery of benefits. Further studies focusing particularly on the impact of stock optimisation and the management of CDs (Controlled drugs) would be key areas of focus.